Electrochemistry Textbooks for Senior High School Students: Need Analysis - R.M. Helmy Sujana; Nuriman Nuriman; Wachju Subchan (Department of Chemistry, Universitas Negeri Malang, 2025)
This study aims to determine the learning resources, methods, and media teachers commonly use for chemistry instruction. It also seeks to assess students' utilisation of textbooks and teaching materials, how they obtain learning resources, the electrochemistry topics that students find challenging, and the characteristics of textbooks they desire. Data regarding students' scientific literacy skills were gathered using the TOSLS instrument, and student responses were collected through a questionnaire administered via Google Forms, which included 12 questions. The scientific literacy skills assessment results yielded a score of 55.28, placing it in the low category. The findings from the questionnaire revealed: 1) Teachers prefer using resources from the internet; 2) Teachers more frequently utilise lecture and assignment methods; 3) Teachers more often employ blackboard media; 4) Students do not fully utilise textbooks and teaching books; 5) Students primarily acquire textbooks and teaching materials by borrowing from the library; 6) Students face difficulties when studying chemistry books, particularly with electrochemistry topics and voltaic cell materials; and 7) Students desire textbooks that feature chemical representation characters.